1995
DOI: 10.1300/j090v11n01_09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Professional Advertising and Its Managerial Implications

Abstract: This study investigated whether there are any differences among four professional groups-physicians, dentists, attorneys, and accountants--regarding professional advertising; their differential use of various advedsing media; and investigation of some segmentation variables. Based on a sample of Wisconsin professionals this study found several interesting results: (1) accountants are the most favorably disposed to advertising among the four professional groups, (2) younger practitioners and those in practice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This may reflect positive attitudes about marketing and its application, together with genuine concerns about providing better service to clients. If this is the case, then there exists support in the data for Marks and Moon's (1994) study which found that lawyers who advertised in more than just the Yellow Pages had more favourable attitudes towards advertising (i.e., were more market oriented) than those who contained themselves to the Yellow Pages or did no advertising at all. Also, there appears to be support for Kohli and Jaworski's (1990) research on the connection between producing a client newsletter and being marketing oriented and client focussed.…”
Section: Marketing and Client Newslettersmentioning
confidence: 93%
See 1 more Smart Citation
“…This may reflect positive attitudes about marketing and its application, together with genuine concerns about providing better service to clients. If this is the case, then there exists support in the data for Marks and Moon's (1994) study which found that lawyers who advertised in more than just the Yellow Pages had more favourable attitudes towards advertising (i.e., were more market oriented) than those who contained themselves to the Yellow Pages or did no advertising at all. Also, there appears to be support for Kohli and Jaworski's (1990) research on the connection between producing a client newsletter and being marketing oriented and client focussed.…”
Section: Marketing and Client Newslettersmentioning
confidence: 93%
“…In fact, professional services marketing has been a relatively neglected area in terms of academic research. Research has tended to concentrate on attitudes towards advertising and intentions to use it (Moser and Johns 1996;Crane 1995;Marks and Moon 1994;McCann, Stern and Muehling 1991;MacDonald and Raymond 1991;Hite and Fraser 1988). Over time, it has become widely recognised that marketing is no longer seen as something solely relevant to commercial organisations.…”
Section: Literature Reviewmentioning
confidence: 99%